Bible story book; a complete narration from Genesis to Revelation for young and old. - Elsie E. Egermeier (Elsie Emilie), 1890-1986.; Arlene S. Hall (Arlene Stevens), 1923-; Clive Uptton (Anderson, Ind. Warner Press, 1969)
Three hundred and twelve stories from the Old and New Testaments with color illustrations by the British artist Clive Uptton.
"Standard edition."
Keywords: Holy Bible Texts and Translations (3fUhU hJQLeGJ GdcJGH GdebOSs; Bible stories, English. -- Bible; Bible stories